A preliminary study on the Orchids of National Botanical Garden, Mirpur, Dhaka, Bangladesh (Jahangirnagar University Journal of Biological Sciences, 2016)
Abstract not availableJahangirnagar University J. Biol. Sci. 3(2): 81-84, 2014 (December)